Enhancing the design of wine labels - Crichton-Fock, Anders; Spence, Charles; Mora, Maria; Pettersson, Nicklas (Frontiers in Psychology, 2023)
Introduction The knowledge accrued through research in the domain of crossmodal correspondences has had a significant influence on a diverse array of disciplines, including behavioral studies, neuroscience, computational modeling, and notably, marketing, with the objective of aligning sensory experiences to help shape patterns of consumer behavior. A study is reported that explores the extension of these principles to the communication of products having a notably complex sensory profile, specifically within the context of wine. The central aim of the project is to explore the feasibility of using crossmodal communication as a strategic tool to augment the congruence between the consumers’ multisensory expectations and their sensory experiences. For consumers venturing into the realm of wine selection without the advantage of prior tasting experience, it is of paramount importance to possess a robust understanding of the mandated information. This encompasses critical elements such as the wine’s origin, grape varietal(s) used, geographical indications, producer qualifications, and the potential implications of these factors on the final wine product. This level of comprehension stands as a necessary prerequisite, enabling these consumers to make informed choices that align with their preferences, even in the absence of previous sensory encounters. Nonetheless, semiotic investigations underscore the significance attributed to symbolic components such as signs, logos, colors, gestures, and linguistic cues. Research from the field performing multisensory studies, presents a counterpoint to prevailing communication paradigms, advocating for a heightened incorporation of metaphors, analogies, symbols, metonymies, and allegories. This alternative approach aims to enhance the efficacy of communication strategies, offering a more profound and evocative means of conveying intricate messages on a more holistic level. Methods A questionnaire was sent to a specific group of engaged wine consumers (n = 329). Besides questions regarding demographics, purchase behavior, and consumption behavior, the questionnaire included examples of multisensory communication through a selection of symbols, as well as alternative wine information. Results The results showed significant correlations between demographics, consumption behavior, and attitudes toward the tested multisensory symbols and alternative information, thus helping to gain a better understanding of the sensory properties that should be communicated on wine labels. Discussion The findings reported here highlight the effectiveness of visual crossmodal communication as a promising pathway capable of skillfully capturing consumer attributes, conveying multisensory experiences, and portraying the comprehensive timeline of taste evolution. As a result, it assumes a pivotal role as a communicative tool for intricate consumables, like wine, functioning at the crossroads of visual and sensory dimensions.